Предмет: Алгебра,
автор: justnounderstand
Решить уравнение . Срочно!
Приложения:
Ответы
Автор ответа:
0
(3x²-2x)/4-(2x²-2)/3=0
(9x²-6x-8x²+8)/12=0
(x²-6x+8)/12=0
x²-6x+8=0
D=(-6)²-4*8=36-32=4
=(-(-6)+√4)/2=(6+2)/2=4
=(-(-6)-√4)/2=(6-2)/2=2
x=4;2
(9x²-6x-8x²+8)/12=0
(x²-6x+8)/12=0
x²-6x+8=0
D=(-6)²-4*8=36-32=4
=(-(-6)+√4)/2=(6+2)/2=4
=(-(-6)-√4)/2=(6-2)/2=2
x=4;2
Похожие вопросы
Предмет: География,
автор: Аноним
Предмет: Қазақ тiлi,
автор: kizlargul27021973
Предмет: География,
автор: andreybelan7777
Предмет: Математика,
автор: gashimovaamaliya
Предмет: Алгебра,
автор: AustranauT